2020
DOI: 10.1177/1477750920903458
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators, barriers, and recommendations related to the informed consent of Marshallese in a randomized control trial

Abstract: Background The Pacific Islander population is the second fasting growing population in the United States and Arkansas is home to the largest Marshallese population in the continental US. The Marshallese community have significant health disparities with high prevalence of diabetes, heart disease, and obesity compared to the general US population. Using a community-based participatory research approach, researchers and Marshallese community stakeholders identified diabetes as the top health issue for research. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Previous research with the Marshallese community has highlighted Marshallese participants' desire for a simplified consent process and the preference for verbal discussion of study requirements ( 21 ). Therefore, as the health screenings were considered a minimal risk study, a waiver of consent documentation was requested and granted by the University of Arkansas for Medical Sciences Institutional Review Board (IRB #262557).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research with the Marshallese community has highlighted Marshallese participants' desire for a simplified consent process and the preference for verbal discussion of study requirements ( 21 ). Therefore, as the health screenings were considered a minimal risk study, a waiver of consent documentation was requested and granted by the University of Arkansas for Medical Sciences Institutional Review Board (IRB #262557).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were asked to agree to allow UAMS researchers to “use my information for future research related to this study that is approved by the UAMS IRB” and to opt in or out of allowing “UAMS to link information from this study to other UAMS studies I have participated in.” In addition to consenting to participate in a GWG study, the participants were asked the questions in Figure 1. Study results will be disseminated to participants, Marshallese research stakeholders such as federally qualified health centers, community clinics, faith-based organizations and community-based organizations, the broader Marshallese community, and fellow researchers (Purvis et al, 2020, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The CHWs ensured that participants had time for discussion about the study requirements, risks, and benefits in their preferred language. Prior research has shown that time for discussion in a participant's native language is effective in improving participant understanding of the informed consent process (Al Tajir, 2018;Nishimura et al, 2013;Purvis et al, 2020Purvis et al, , 2021. The limitations of the study include a nonrandom, small sample size from one racial group in a single geographic area.…”
Section: Best Practicesmentioning
confidence: 99%
See 1 more Smart Citation